2016
DOI: 10.18203/2320-6012.ijrms20164182
|View full text |Cite
|
Sign up to set email alerts
|

Role of staging laparoscopy in upstaging CT findings and influencing treatment decisions in gastric cancers

Abstract: INTRODUCTIONIt is estimated that 990000 new gastric cancer (GC) cases occur in the world annually.1 In India, the incidence rate of gastric is low compared to that in western countries, and the number of new cases is approximately 34,000. Due to the absence of a mass screening program, more than 80% of all Indian cases are discovered at an advanced stage. Despite significant improvement in preoperative tumour staging, many patients with gastric malignancies are found at exploration to be unable to undergo rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
1
0
5
Order By: Relevance
“…This is consistent with the findings by Indrakumar et al, who assessed the role of staging laparoscopy in gastric tumors. They reported that diagnostic laparoscopy was effectively able to detect distant metastasis in 12 patients which were previously undetected on CT (7) . Another study on gastric tumors reported similar findings (8) .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings by Indrakumar et al, who assessed the role of staging laparoscopy in gastric tumors. They reported that diagnostic laparoscopy was effectively able to detect distant metastasis in 12 patients which were previously undetected on CT (7) . Another study on gastric tumors reported similar findings (8) .…”
Section: Discussionmentioning
confidence: 99%
“…В работах S. Kakroo et al (2013 г.) [16] и A. Indrakumar et al (2013 г.) [17] также выявлено преимущество ДЛ в определении категории Т по сравнению с КТ (76-77% против 65-68%).…”
Section: таблицаunclassified
“…Причины различных заключений о преимуществах того или иного метода могут заключаться в разных подходах к группировке пациентов. Так, во всех приведенных выше зарубежных исследованиях [15][16][17] при сравнении эффективности методик авторы проводили разделение больных на группы в соответствии со степенями опухолевой инвазии T1/2, T3, T4. В нашей работе анализ проводился в группах больных со степенями опухолевой инвазии Т1-3, Т4а, Т4b.…”
Section: таблицаunclassified
See 1 more Smart Citation
“…Одной из основных проблем проведения неоадъювантной терапии у больных раком желудка является недостаточная точность дооперационной (клинической) диагностики и в связи с этим назначение терапии тем больным, которым она не показана. По данным различных авторов, чувствительность КТ в определении категории Т составляет 60-65 %, а категории N -50-78 % [10,11]. В МРНЦ в последние годы последовательно изучались симптомокомплексы распространенности рака желудка, позволившие повысить точность КТ-диагностики до 80 % и более [12].…”
Section: результаты и обсуждениеunclassified